The Effects of Mobile Phone Usage on Students’ Attentiveness in Class at Uganda Christain University. - Prossy Alowo (Uganda Christian University, 2023)
The study sought to examine the effects of mobile phone usage on students’ attentiveness in class at Uganda Christian University. The study was guided by three objectives; to find out effects of mobile phone usage on students’ academic performance, to find out impacts of mobile phones on students’ behavior in class and to suggest possible interventions to reduce mobile phone addiction among students. Chapter two; this chapter contains the literature review of the main purpose of the study; what the previous and other authors have studied about the topic of the study. Chapter three; this chapter reflects the research methodology to be used to collect data for the study. Chapter four; this chapter entails the data presentation and analysis of the collected data. Chapter five; this chapter contains the summary of the findings of the study, the conclusion and the recommendations. It also contains the sample of the questionnaire and interview guide used for the study in obtaining data.
This is a dissertation.